Źródła wiedzy i metody pielęgnacji wyglądu zewnętrznego wśród mieszkańców Polski Wschodniej = Sources of knowledge and appearance upkeep methods among residents of Eastern Poland - Humeniuk, Ewa; Dąbska, Olga; Pawlikowska-Łagód, Katarzyna; Oberda, Katarzyna (Journal of Education, Health and Sport, 2017)
Humeniuk Ewa, Dąbska Olga, Pawlikowska-Łagód Katarzyna, Oberda Katarzyna. Źródła wiedzy i metody pielęgnacji wyglądu zewnętrznego wśród mieszkańców Polski Wschodniej = Sources of knowledge and appearance upkeep methods among residents of Eastern Poland. Journal of Education, Health and Sport. 2016;6(11):329-340. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.176626 http://ojs.ukw.edu.pl/index.php/johs/article/view/4003 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.11.2016. Revised 12.11.2016. Accepted: 21.11.2016. Źródła wiedzy i metody pielęgnacji wyglądu zewnętrznego wśród mieszkańców Polski Wschodniej Sources of knowledge and appearance upkeep methods among residents of Eastern Poland Ewa Humeniuk1, Olga Dąbska1, Katarzyna Pawlikowska-Łagód2, Katarzyna Oberda1 1Zakład Patologii i Rehabilitacji Mowy, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 2Zakład Etyki i Filozofii Człowieka, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie dr hab. n. o zdr. Ewa Humeniuk1, mgr Olga Dąbska1, mgr Katarzyna Pawlikowska-Łagód2, mgr Katarzyna Oberda1 Streszczenie Wstęp. Wygląd zewnętrzy zdaniem wielu osób odgrywa kluczową rolę w funkcjonowaniu społecznym. Wizje piękna kreowane są na podstawie licznych czynników, z których największe znaczenie przypisuje się wszechobecnym mass mediom. Cel pracy. Celem pracy było zbadanie źródeł wiedzy i sposobów dbania o wygląd zewnętrzny mieszkańców Polski Wschodniej Materiał i metody. Badania przeprowadzono wśród 61 osób. Narzędzie badawcze stanowił autorski kwestionariusz. Wyniki. Badani zwracają uwagę na wizję pięknego ciała kreowanego w mediach, choć nie zawsze się z nią zgadzają. W celu poprawy urody ankietowani stosują kosmetyki nawilżające, redukujące zmarszczki oraz balsamy ujędrniające. Większość nie poddaje się drastycznym dietom ani suplementacji, za to popularne jest uprawianie sportu. Wnioski. Dla mieszkańców Polski Wschodniej wygląd zewnętrzny jest ważny. Podejmowane w celu zapewnienia ładnego wyglądu aktywność ruchowa oraz prawidłowe odżywianie wpływają pozytywnie nie tylko na wygląd zewnętrzny, ale i na ogólny stan zdrowia. Słowa kluczowe: wygląd zewnętrzny, ciało, uroda, kanon piękna Sources of knowledge and appearance upkeep methods among residents of Eastern Poland Summary Introduction. According to many, outside appearance plays a key role in social functioning. Ideals of beauty are created on the grounds of various factors, ubiquitous mass media being the most important one. Goal of work. Analysis of sources of knowledge and appearance upkeep methods among residents of Eastern Poland. Data and methods. The research was conducted on the group of 61 people. Authorial questionnaire was the research tool. Results. The surveyed pay attention to the ideals of beauty portrayed by the media but they do not always agree with them. The surveyed use moisturizers, beauty products reducing wrinkles and skin firming creams in order to improve their appearance. Most of them are not on drastic diets and they do not use supplementation but they do engage in physical activities. Conclusion. Outside appearance is important for residents of Eastern Poland. Undertaken physical activities and proper nutrition have positive effects not only on the outside appearance but also on the general health condition. Key words: physical appearance, body, beauty, beauty canon